Passage to Nowhere - Ikram Sehgal (Dhaka Probe, 2009)
On Pakistan's foreign policy during the period December 1987 to June 2003.
Include Illustration and Index
Keywords: Pakistan -- Foreign Relations -- 1971- -- Pakistan -- Politics and Government -- 20th Century -- Pakistan -- Politics and government -- 21st Century